Non-HDL-C/HDL-C Ratio and N-Terminal Pro-B-Type Natriuretic Peptide in the general and hospital-based population: a cross-sectional validation study - Xie, Haitao; Li, Jianghong; Shen, Le; Yu, Peng; Wang, Shi; Chen, Xiaohu; Tang, Shuhua (Frontiers in Endocrinology, 2026)
BackgroundAs an innovative composite lipid assessment index, the Non-HDL-C/HDL-C Ratio (NHHR) offers a more holistic appraisal of lipid metabolic profile. This investigation seeks to elucidate the association between NHHR and elevated N-Terminal Pro-B-Type Natriuretic Peptide (NT-proBNP) levels in the general and hospital-based population.MethodsThe research participants were drawn from the National Health and Nutrition Examination Survey (NHANES, 1999-2004, Group 1) and from hospital inpatients within the Cardiology Department of Jiangsu Province Traditional Chinese Medicine Hospital (JSHTCM, January to June 2025, Group 2). We preliminarily evaluated and adjusted for the original prevalence and age-standardized prevalence of NT-proBNP elevation in different populations. A stepwise inference generalized linear modeling approach was employed to explore the association between NHHR and NT-proBNP elevation, with a restrictive cubic spline (RCS) used to visualize the simulations, evaluated correlation trends through trend tests, observed inter-group differences through subgroup analyses, assessed overall population results robustness through interaction tests. Additionally, based on the non-linear associations, we further refined the analysis through threshold and saturation effects, as well as piecewise regression analysis.ResultsIn Group 1, females exhibited a higher age-standardized prevalence of NT-proBNP elevation than males (20.51% vs. 10.74%), which declined progressively as NHHR levels increased. Generalized linear models demonstrated a notable inverse link between NHHR and NT-proBNP elevation in both groups, and the results of the RCS plots are largely consistent with the findings from the generalized linear models. Additionally, further threshold and saturation effects analysis identified 4.3 as the NHHR inflection point in Group 1. Piecewise regression analysis indicated that below this threshold, higher NHHR corresponded to a reduced likelihood of NT-proBNP elevation. Specifically, for each standard unit increase in NHHR, the probability of elevated NT-proBNP decreased by 24% [HR (95% CI): 0.76 (0.68, 0.86), P < 0.001]. When NHHR exceeded the inflection point, the association between the two variables no longer remained significant.ConclusionsIn the general and hospital-based population, a negative correlation was identified between the increase in NHHR and NT-proBNP elevation levels, corroborating the utility of NHHR as a simple composite lipid index for identifying changes in NT-proBNP.